Postharvest senescence of Consolida ajacis inflorescences - Finger, Fernando Luiz; Carneiro, Tânia Forster; Barbosa, José Geraldo (Pesquisa Agropecuaria Brasileira, 2004)
This work had the objective of evaluating the influence of inhibitors of ethylene action and synthesis on the longevity, respiration and ethylene production of Consolida ajacis Nieuwl. inflorescences. The inflorescences were harvested and immediately pulsed with 5% sucrose, 1 mM silver thiosulfate (STS) combined or not with 5% sucrose for 30 minutes or sprayed with 0.5, 1.0, 1.5 and 2.0 mM aminooxiacetic acid (AOA) and 5, 10, 15 and 20 mM acetylsalicylic acid (ASA). Flower senescence of C. ajacis was characterized by the presence of climacteric ethylene and CO2 production, reaching maximal evolution at the sixth day after harvest, which were coincident with the later phases of the flower abscission and wilting. Longevity of flowers pulsed with 1 mM STS increased by 2.46-fold compared to control flowers. However, when STS was mixed with 5% sucrose, a decrease on longevity was observed. Pulsing the flowers with 5% sucrose or spraying with 2 mM AOA or 20 mM ASA neither increased the longevity nor inhibited the climacteric respiration and ethylene production. The treatment with STS was effective in reducing the respiration and ethylene evolution by the flower.
Keywords: pulsing; longevity; ethylene; respiration